Antunes de Oliveira: trajetória educacional e protagonismo no debate da LDB 4.024/61 - Chaves, André Câmara (2021)
This research aims to analyze significant aspects of the educational trajectory of Antunes de Oliveira, focusing on the period from 1940 to 1961. The needs that he met from his social work as a Baptist pastor in the neighborhood of Educandos, in the city of Manaus (AM), added to his worldview, equated to a set of contingent actions. Antunes became a politician who participated intensely in the educational debate in the National Congress, around the approval of the first Law of Guidelines and Bases of National Education in 1961.